Rates of Minor Adverse Events and Health Resource Utilization Postcolonoscopy - Vladimir Marquez Azalgara; Maida J Sewitch; Lawrence Joseph; Alan N Barkun (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Little is known about minor adverse events (MAEs) following outpatient colonoscopies and associated health care resource utilization.